Finding a comprehensive dispute resolution mechanism for compensating obstetric injuries in Malaysia: Issues and challenges - Mohd Najid, Khadijah; Jahn Kassim, Puteri Nemie (Ahmad Ibrahim Kulliyyah of Laws (AIKOL), International Islamic University Malaysia, 2017)
Victims of obstetric injuries usually suffer life-long disabilities that tend to deprive them of years of enjoyment in life, independence and productivity. As these injuries occur on the victims early in life, the costs of medical and nursing care are usually enormous. This subsequently imposes stressful and heavy burden on the family members who will resort to litigation as means of procuring monetary compensation. However, proving that such injuries were attributable to negligence is not an easy task and the affected parties are usually subjected to various hazards of litigation including excessive cost, delays and inconsistencies of outcome. The many hurdles of pursuing a medical negligence suit in court has discouraged victims of obstetric injuries from obtaining adequate compensation. The ‘name, blame and shame’ culture in litigation tend to destroy the relationship of trust and confidence between a doctor and his patient and this ultimately, hinders any possibilities of amicable settlements and future rehabilitation. The quality of healthcare system may thus, be compromised as doctors become more and more defensive in their practice and constantly, submitting themselves to the ‘conspiracy of silence.’ Further, as the premium for medical indemnity insurance for obstetricians escalate, many obstetricians tend to leave the practice leading to reduced availability of obstetric care. Hence, the inherent difficulties in establishing negligence and the hazards of litigation have triggered the move by many jurisdictions to find alternative methods in compensating for birth injuries. Presently, in Malaysia, several incentives have been made to encourage affected parties to avoid litigation in gaining compensation for birth injuries. This includes the creation of several platforms for the affected parties to channel their complaints as well as encouraging out of court settlements through mediation, arbitration and the payment of ex gratia. However, the absence of any specific laws governing the practice of ex gratia poses a threat of unjust interchanges between the affected parties and the withdrawal of cases in exchange of such payment deters proper disclosure of adverse events. Thus, it is imperative that a comprehensive dispute resolution mechanism for obstetric cases is introduced in Malaysia, which is capable of delivering timely as well as adequate compensation to victims of obstetric injuries in a less adversarial manner and at the same time, ensuring that the quality of healthcare is not compromised in any aspects.